The second international school of young ethnosociologists «Traditions and social cultural transformations: The theory and technique of ethnosocial researches» - Madiukova, Svetlana A.; Erokhina, Elena A. (The New Research of Tuva, 2009)
An overview of the work of the Second international school of young ethnosociologist "Traditions and socio-cultural transformations: theory and methods of social research" (Republic of Altai, Russia, June-July 2008)
Keywords: overview; international school; youth in science; sociology; social transformation; tradition; culture; Altai Republic